In vitro ischemia triggers a transcriptional response to down-regulate synaptic proteins in hippocampal neurons - Fernandes, Joana (2014)
Transient global cerebral ischemia induces profound changes in the transcriptome of brain cells, which is partially associated with the induction or repression of genes that influence the ischemic response. However, the mechanisms responsible for the selective vulnerability of hippocampal neurons to global ischemia remain to be clarified. To identify molecular changes elicited by ischemic insults, we subjected hippocampal primary cultures to oxygen-glucose deprivation (OGD), an in vitro model for global ischemia that resulted in delayed neuronal death with an excitotoxic component. To investigate changes in the transcriptome of hippocampal neurons submitted to OGD, total RNA was extracted at early (7 h) and delayed (24 h) time points after OGD and used in a whole-genome RNA microarray. We observed that at 7 h after OGD there was a general repression of genes, whereas at 24 h there was a general induction of gene expression. Genes related with functions such as transcription and RNA biosynthesis were highly regulated at both periods of incubation after OGD, confirming that the response to ischemia is a dynamic and coordinated process. Our analysis showed that genes for synaptic proteins, such as those encoding for PICK1, GRIP1, TARPc3, calsyntenin-2/3, SAPAP2 and SNAP-25, were downregulated after OGD. Additionally, OGD decreased the mRNA and protein expression levels of the GluA1 AMPA receptor subunit as well as the GluN2A and GluN2B subunits of NMDA receptors, but increased the mRNA expression of the GluN3A subunit, thus altering the composition of ionotropic glutamate receptors in hippocampal neurons. Together, our results present the expression profile elicited by in vitro ischemia in hippocampal neurons, and indicate that OGD activates a transcriptional program leading to down-regulation in the expression of genes coding for synaptic proteins, suggesting that the synaptic proteome may change after ischemia.